A 3-bp Deletion VK600-1E in the BRAF Gene Detected in a Young Woman with Papillary Thyroid Carcinoma - Dvorakova, S; Sykorova, V; Vaclavikova, E; Sykorova, P; Vlcek, P; Kodetova, D; Lastuvka, P; Betka, J; Mokrejs, M; Vcelak, J; Bendlova, B (Endocrine pathology, 2015)
Papillary thyroid cancer (PTC) derived from follicular cells is a frequent thyroid tumor. The incidence of this type of malignancy is still growing worldwide. Several major genetic causes are recognized to cause PTC-mutations in the BRAF and RAS genes or rearrangements with the RET proto-oncogene. The most common genetic change found in PTC is a V600E mutation in the BRAF gene presented in 36-69 % of all PTC cases. For routine purposes, several methods were developed to selectively detect only this mutation. However, these methods miss other mutations in the BRAF gene located elsewhere. We focused on the analysis of the exon 15 of the BRAF gene by next-generation sequencing. Here we report a three nucleotide deletion VK600-1E in one patient and present this finding in the context of 13 previously described PTC cases with this deletion. Our patient is the second youngest one among the reported cases. Clinical features of PTC patients with VK600-1E are summarized. For the future, it is important to evaluate genotype-phenotype characteristics of patients with rare BRAF mutations and to follow up them for years.
Keywords: BRAF gene; Carcinoma, Papillary; Česká republika; protoonkogen Mas; Adult; nádory štítné žlázy; Proto-Oncogene Mas; Sequence Deletion; Czech Republic; sekvenční delece; Carcinoma; Papillary thyroid cancer; ženské pohlaví; Thyroid Neoplasms; Humans; Thyroid Cancer, Papillary; Deletion; Proto-Oncogene Proteins B-raf; Rare mutation; papilární karcinom štítné žlázy; protoonkogenní proteiny B-Raf; dospělí; Female; papilární karcinom; lidé; karcinom